Climate change effect on dairy in north eastern hills of India - FEROZE, SHEIKH MOHAMMAD; RAHMAN, SAIDUR; SINGH, KOIJAM JOHNY; SINGH, RAM; DKHAR, SAO EVALWELL (The Indian Journal of Animal Sciences, 2019)
The experimental evidences on the effect of climate change on dairy animals are sufficient but primarily restricted to developed production system of plain land. Hence, this paper assessed the effect of climate change on dairy in the north eastern Himalayan states of India. A random sample of 240 farm households from Asom and Nagaland were interviewed and a case study was conducted in Mizoram. It was found that the livestock compositions have changed and the number of animal per household decreased during drought. The availability of fodder and pasture dwindled which increased the time spent on collection of fodder; and the milk yield of the dairy cows declined. Just & Pope stochastic production function revealed that the increase in maximum temperature is expected to increase the variability in milk yield in the north eastern hill states as the heat stress reduces the milk yield of dairy animals. Hence, location specific scientific housing and feed management may be adopted to reduce the negative effect of climate change on dairy animals.